Brain Dominance as a Tool for Management Career Development in Law Firms and Legal Advisory Services - Villasmil Pirela, Nerio Luis; Rivas Carruyo, Benylé Josefina; Bracho Cordero, Elias José (Frónesis, 2024)
This paper develops a way to test an overview on the contribution that the theory of the psychological profile of the Brain dominances give areas of human talent development Law Firms and Legal Advice. This, in order to use the principles of it, in the career development of potential occupants for the post of manager. This analysis and through descriptive research, it explores how the introduction of this theory raised by Benziger (1994) in the process of identifying strengths natural brain that result in behaviors, attitudes and specific characteristics in people predominantly manifest any of the four brain modes set by the author (front left, front right, left and right basal basal). Based on these considerations, it would be possible to bring about more effective recruiting and training future manager, attending not only to qualifications, experience and / or qualifications achieved by it, but also to preferences regarding activities of the ownership and specificity assigned area management (production, finance, marketing, etc.). This would facilitate a worker to have prepared, committed and happy with the performance of activities that are in line with typical features of their biology and brain structure. This, along with ensuring that the training process is effective and that the investments made in the development of potential career manager, are against the practice areas related to his cerebral dominance.